Modest rates and wide variation in timely access to repeat kidney transplantation in the United States. Issue 3 (15th November 2019) - Schold, Jesse D.; Augustine, Joshua J.; Huml, Anne M.; O'Toole, John; Sedor, John R.; Poggio, Emilio D.
Abstract : Success of transplantation is not limited to initial receipt of a donor organ. Many kidney transplant recipients experience graft loss following initial transplantation and the benefits of expedited placement on the waiting list and retransplantation extend to this population. Factors associated with access to repeat transplantation may be unique given experience with the transplant process and prior viability as a candidate. We examined the incidence, risk factors, secular changes, and center‐level variation of preemptive relisting or transplantation (PRLT) for kidney transplant recipients in the United States with graft failure (not due to death) using Scientific Registry of Transplant Recipients data from 2007 to 2018 (n = 39 557). Overall incidence of PRLT was 15% and rates of relisting declined over time. Significantly lower PRLT was evident among patients who were African American and Hispanic, males, older, obese, publicly insured, had lower educational attainment, were diabetic, had longer dialysis time prior to initial transplant, shorter graft survival, longer distance to transplant center, and resided in distressed communities. There was significant variation in PRLT by center, median = 13%, 10th percentile = 6%, 90th percentile = 24%. Cumulatively, results indicate that despite prior access to transplantation, incidence of PRLT is modest with pronounced clinical, social, and center‐level sources of variation suggesting opportunities to improve preemptive care among patients with failing grafts. Abstract : Despite significant advantages and established relationships with transplant centers, kidney transplant recipients with failing grafts are infrequently listed preemptively for retransplantation, with wide variation in frequency based on patient characteristics and initial transplant center.